The Effect of Digital Marketing Training on Improving Entrepreneurship Skills of PT Independent Study Participants. Arkatama Multi Solusindo Batch 2 - Pratami, Anggiet Rachmatya; Nandang, Nandang; Nurfitriya, Mira (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
The purpose of this study is to provide an overview of training and entrepreneurship skills enhancement, as well as to determine the impact of digital marketing training on improving the entrepreneurship skills of participants in the Independent Study Program at PT. Arkatama Multi Solusindo Batch 2. The research method used is quantitative with a descriptive and verificative approach. The population of this study consists of 284 participants of PT. Arkatama Multi Solusindo Batch 2, the sample was taken using a non-probability purposive sampling technique totaling 71 participants. Data analysis and testing were conducted using SPSS version 27. The analysis methods include instrument tests, classical assumption tests, and simple linear regression tests. From all the tests performed, the result obtained is that H1 is accepted, meaning that there is a positive influence of digital marketing training on the improvement of entrepreneurship skills. If training is provided, the participants' entrepreneurship skills can improve. Conversely, if training is not provided, the participants' entrepreneurship skills will not improve. This shows that training plays an important role in enhancing entrepreneurship skills.